Evaluation of a new lactation device 'Lactamo' designed to apply massage, heat or cold, and compression to the breast - Linda Sweet; Vidanka Vasilevski (BMC, 2022)
Abstract Background Common approaches to manage breastfeeding problems such as pain, blocked ducts, and milk production issues include breast compression, breast massage, application of warmth or cold, medications, and breastmilk expression. Several devices are available to apply heat or cold to the breast, however, none promote breast compression and/or massage simultaneously. A new device 'Lactamo' has been developed to address this. Methods This study was a pre-market evaluation of the Lactamo device. The aims were to determine user safety, and satisfaction of Lactamo. The study was conducted in an Australian tertiary maternity hospital in 2019-2020. Women who were less than 3 months post-partum and were currently breastfeeding participated in the study. We conducted structured telephone surveys at 1 and 4 weeks post supply of Lactamo. Questions included demographic information, feedback on safety, usage, and perceived benefits of Lactamo. Results The cohort (n = 30) consisted of equal number of primiparous and multiparous women, 50% were born in Australia and the remainder from 11 other countries. A total of 41 telephone surveys were conducted with 27 women. Of these, 26 (96%) had used Lactamo, and the one that did not, felt she did not have a lactation concern to warrant using it. All women indicated that the device was safe to use and had no concerns, apart from one woman who experienced itching because of the device but continued to use it over clothing as she found it beneficial. Most women used it at room temperature or warmed. The frequency of use varied from once per week (17%) to daily (33%), and use was often prompted by a lactation concern such as engorgement, pain, blocked ducts, and low supply. Conclusion Lactamo was found to be safe, and a valuable aid for breastfeeding women. More research is needed to understand the efficacy of the device in treating breastfeeding problems such as pain, blocked ducts, and milk production issues.